Dental students' knowledge and perception of elderly in relation to geriatric dentistry training - Husna AA; Robaiyah K; Tanti IR (Penerbit UKM, 2009)
Dental students need to be equipped with skills, knowledge and positive attitudes while providing dental care to the elderly. Reports from Ministry of Health Malaysia indicated that the prevalence of dental caries and periodontal disease was high among older people in the country. The aim of this study was to assess the knowledge and perception of final year dental students towards the elderly in relation to training of geriatric dentistry in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). All the final year dental students were required to complete a questionnaire that comprised of 3 sections: 1) Palmore’s Facts on Aging Quiz II, 2) Oral health and social concerns of patients, and 3) Perception towards the teaching of geriatric dentistry. A total of 83 students participated in the study. Twenty-four per cent (n=20) scored more than 70% to questions on knowledge about older people and 73% (n=61) scored between 50-70%. The students had ranked physical disability, transportation problems and complex and overlapping priorities as reasons for elderly not keeping to their appointments. Majority of the students reported that lack of educational resource materials and very minimum clinical sites experience were the main barriers faced during the course. In conclusion, majority of the students had moderate to good knowledge about older people and were able to recognize issues of social concerns that can influence their oral health. In general, there were not many changes in the perceived competencies of managing older patients following the geriatric module.